Definition of legal consciousness as a legal phenomenon: interdisciplinary approach - Vershok, Irina L. (Journal of the Belarusian State University. Law, 2022)
The article provides a critical analysis of the classical defnition of legal consciousness as a form of objective reality reﬂection in the form of a set of ideas, views, assessments and feelings. The author signs of legal consciousness as a phenomenon of a complex nature which are social, psychological, biological and legal are considered. An analysis of the main features of legal consciousness is given. Legal consciousness is a process of perception, reﬂections, comprehension and interpretation of information, that proceed when a person adapts to the environment. Legal consciousness is intentionally directed to the object of social action or legal interaction, as well as to the rule of law that mediates it. Legal consciousness is closely connected with its bearer. The ability of the subject to direct the intentionality of its legal consciousness both to the external object of the surrounding legal reality and to itself predetermines the need to distinguish the subject in law and legal subjectivity. Legal consciousness has the property of tension. The dynamics of legal consciousness is determined by its temporality that has specifc features both for an individual subject and for a collective.